Esthetic smile rehabilitation of enamel hypomineralized teeth with E-max prosthesis: Case report - AlHanouf M. Alkaabi; Abdulkareem A. AlHumaidan; Firas K. AlQarawi; Faris A. AlShahrani (Elsevier, 2019)
Developmental enamel hypomineralization is a condition affect quality of enamel result in low translucency and opacity area that compromise patient smile. Lithium disilicate Emax prosthesis report a superior properties in esthetic treatment. This report is aimed to determine the effectiveness of lithium disilicate (E-max) prosthesis in managing esthetic demand of patient with enamel hypomineralized teeth. Keywords: Enamel hypomineralization, Lithium disilicate, E-max, Rehabilitation, Esthetic, Crown lengthening